2022
DOI: 10.3390/nu14122401
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Ginseng (Panax) on Human Prediabetes and Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: Results from different clinical trials on the effects of ginseng on prediabetes and type 2 diabetes (T2DM) are still inconsistent. To fill this knowledge gap, we investigated the overall effects of ginseng supplementation on improving cardiometabolic biomarkers among these patients. A systematic literature search was conducted on PubMed/MEDLINE, Scopus, Web of Science, and Cochrane library. A random-effect model was applied to estimate the weighted mean difference and 95% CI for each outcome. Overall, 20 eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 82 publications
0
31
0
Order By: Relevance
“…Many functional plants and their bioactive components have been demonstrated to possess anti-diabetic effects, such as tea ( 49 ), sweet tea ( 50 ), ginseng ( 29 ), citrus ( 51 ), pomegranate peel ( 52 ), and some medicinal plants ( 53 ). The present meta-analysis investigated the effectiveness of N. sativa consumption on cardiometabolic indicators among individuals with prediabetes and T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many functional plants and their bioactive components have been demonstrated to possess anti-diabetic effects, such as tea ( 49 ), sweet tea ( 50 ), ginseng ( 29 ), citrus ( 51 ), pomegranate peel ( 52 ), and some medicinal plants ( 53 ). The present meta-analysis investigated the effectiveness of N. sativa consumption on cardiometabolic indicators among individuals with prediabetes and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity was determined by the I 2 statistic and Cochrane's Q test. I 2 -value > 50% or P < 0.05 for the Q -test was characterized as significant between-study heterogeneity ( 29 , 30 ). We used a random-effects model that considers the study variations to determine the overall effect sizes.…”
Section: Methodsmentioning
confidence: 99%
“…Frontiers in Pharmacology frontiersin.org Ghavami et al, 2020;Miraghajani et al, 2020;Lee et al, 2021;Sha'ari et al, 2021;Ikeuchi et al, 2022;Lee et al, 2022;Luo and Huang, 2022;Naseri et al, 2022;Park et al, 2022;Zhu et al, 2022), whereas two focused on eligible combinations (such as with usual medication) (Duan et al, 2018;Zhu et al, 2021). Most studies reported the type of ginseng, which mainly included Panax ginseng, Panax notoginseng, Panax quinquefolius, and red ginseng.…”
Section: Literature Search and Characteristics Of The Included Studiesmentioning
confidence: 99%
“…6 T2D is caused mainly due to pancreatic β cell dysfunction or insulin resistance, accounting for the majority of diabetes. 7 GD is the diabetes that occurs or is first diagnosed during pregnancy. 8 Besides, prediabetes has also attracted increasing attention, and is characterised by impaired glucose tolerance and is more likely to develop into T2D in the future.…”
Section: Introductionmentioning
confidence: 99%